(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study undertaken aims to investigate the effect of financial development and sector specific stock market indices on the respective sector’s growth for the Indian economy and uses quarterly time-series data ranging from 2005-06: Q1 to 2019-20: Q4. The study applies Autoregressive Distributed Lag (ARDL) bounds test, concluding the existence of a long-run co-integrating relationship between sector-specific GDP with stock market indices and financial development in India. The granger causality tests conclude the existence of a bi-directional causality running between financial development and sector-specific economic growth. The study found that there exists a two-way causality between sectoral stock market development and sector-specific economic growth only in the services sector while only a unidirectional causality runs from stock market growth to GDP growth in the manufacturing sector, and there exists no causality in the utility sector.